Breast Refusal and Maternal and Perinatal Risk Factors in the Newborn Period From a Single Center in Şanlıurfa - Bülent Güneş; S. Songül Yalçın (Galenos Publishing House, 2023)
The many benefits of breastfeeding for both the mother and infant are well known. Therefore, the conditions that influence breastfeeding are important. Therefore, we investigated the frequency of breast refusal in the newborn period and the associated maternal perinatal risk factors at an Şan Med Hospital in Şanlurfa. A total of 407 mother-infant pairs fulfilling the study's inclusion criteria were enrolled. The percentage of breast refusal in infants was higher in young maternal and paternal age (<25 years), being the first child, and active or passive smoking exposure of the mother during pregnancy. The percentage of breast rejection was lower when the baby started to be breastfed within the first hour of birth. The percentages of infants experiencing breast rejection were found to be significantly higher in the absence of skin-to-skin contact following delivery and in the presence of prelactal feeding at the first 3 days than in their counterparts. The rate of breast rejection was found to be higher in infants fed with mixed or formula compared with infants fed only breast milk during the last 24 h. Multiple logistic regression analysis determined that the risk of breast rejection was higher in maternal smoking/exposure during pregnancy [adjusted odds ratio (aOR): 3.19, 95% confidence interval (CI): 1.01-10.06] and delayed initiation of breastfeeding after the first hour (aOR: 3.45, 95% CI: 1.09-11.0). Being in a smoke-free environment for pregnant women should be supported by an indoor smoking ban, and early initiation of breastfeeding in the first hour after birth should be encouraged.